2003
DOI: 10.1152/ajpheart.00899.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid modification of the glycocalyx caused by ischemia-reperfusion is inhibited by adenosine A2Areceptor activation

Abstract: Ischemia-reperfusion (I/R) has been shown to cause microvascular dysfunction and to alter the appearance of the glycocalyx in electron micrographs. We hypothesized that I/R injury might alter the structure and/or permeability of the glycocalyx. Prior work had shown a role for adenosine in protection from I/R injury, and, therefore, we also explored the idea that activation of the adenosine A2A receptor would attenuate I/R glycocalyx injury. Here, we report that I/R causes a rapid and dramatic decrease in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 45 publications
(89 reference statements)
6
73
0
1
Order By: Relevance
“…Numerous studies have shown that the 70-kDa dextran does not penetrate the glycocalyx and is therefore retained in the vasculature, whereas the 40-kDa dextran penetrates the glycocalyx within minutes and may leave the vasculature (27,28,40). For permeability testing of the glycocalyx, use was made of this different behavior of both dextrans by examing the dextran concentration, normalized to the doses given, for the first 30 min after administration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that the 70-kDa dextran does not penetrate the glycocalyx and is therefore retained in the vasculature, whereas the 40-kDa dextran penetrates the glycocalyx within minutes and may leave the vasculature (27,28,40). For permeability testing of the glycocalyx, use was made of this different behavior of both dextrans by examing the dextran concentration, normalized to the doses given, for the first 30 min after administration.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence demonstrated a role of the glycocalyx in models of ischemiareperfusion injury, inflammation, and altered lipoprotein levels (26,28,38). To our knowledge, no study has examined whether hyperglycemia affects the glycocalyx.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies, antioxidants rapidly reversed glycocalyx damage, including polyethylene glycol [46], NO [34], adenosine agonists [45], TNF-a inhibitors [43], allopurinol, heparin and hyaluronan [47]. These agents reduced oxidative stress, cellular transudate, glycocalyx shedding and restored glycocalyx volume.…”
Section: Damage To the Endothelial Surface Layermentioning
confidence: 98%
“…Its properties, such as capillary barrier function and interaction with plasma components, have been studied (20). The glycocalyx consists of protein, glycolipid, and proteoglycans, including exposed charged groups, and also contains membranebound molecules, such as selectins and integrins (22, 25), involved in immune reactions and inflammatory processes (13,18,29).The intracellular uptake of macromolecules is possibly regulated by glycocalyx properties, such as surface charge and morphological barriers. The glycocalyx surface has a negative charge because the glycocalyx has some acidic mucopolysaccharide sidechains (GAG), which contain many carboxyl and sulfate groups.…”
mentioning
confidence: 99%